2022
DOI: 10.1111/vru.13154
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic quantitative evaluation of acute and chronic renal disease using the renal cortical thickness to aorta ratio in dogs

Abstract: The renal cortical thickness (RCT) has been correlated with renal function. Previous studies have also reported that the RCT:Abdominal aorta(Ao) ratio is constant in normal dogs with various physical factors. This multi‐center, retrospective, analytical study aimed to determine if there are differences between actual RCT and predicted value of RCT considering physical factors in dogs with acute or chronic renal disease. We also aimed to demonstrate whether the RCT and Ao ratio index would be useful for evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In the current study, the RCT: Ao ratio was higher compared with values reported in earlier studies. 8,29 This difference in values could be attributed to the lower mean body weight of the subjects in previous reports. The RCT:Ao ratio exhibited a negative correlation with body weight.…”
Section: Parametersmentioning
confidence: 81%
See 3 more Smart Citations
“…In the current study, the RCT: Ao ratio was higher compared with values reported in earlier studies. 8,29 This difference in values could be attributed to the lower mean body weight of the subjects in previous reports. The RCT:Ao ratio exhibited a negative correlation with body weight.…”
Section: Parametersmentioning
confidence: 81%
“…These observations were recorded in the present study as per Bragato et al 1 The quantitative parameters, including length (L), breadth (B), height (H), the thickness of the renal cortex (RCT), the thickness of the renal medulla (RMT), and the diameter of the aorta (Ao) in centimeters (cm) caudal to the origin of the left renal artery, were recorded as per earlier reports (Figure 1). 6,8,28,29 At least two measurements were taken for L, B, H, RCT, and RMT, and the average of the respective measurements was recorded for further calculations. From these measurements, L:Ao, B:Ao, H:Ao, cortico-medullary (CM), and RCT:Ao ratios were derived.…”
Section: B-mode Ultrasonographic Data Collection and Analysismentioning
confidence: 99%
See 2 more Smart Citations